Reprofiling lamivudine as an antibiofilm and anti-pathogenic agent against Pseudomonas aeruginosa - Othman Yahya Alyahyawy; Raafat M. Munshi; Shaimaa M. Badr-Eldin; Hibah Mubarak Aldawsari; Walaa Abualsunun; Hisham A. Abbas; Ibrahim M. Salem; Wael A. H. Hegazy; Shaimaa I. Nazeih (AMB Express)
Abstract Resistance to antibiotics is a critical growing public health problem that needs urgent action to combat. To avoid the stress on bacterial growth that evokes the development of resistance, anti-virulence agents can be an attractive strategy as they do not target bacterial growth. There are FDA approved drugs have been screened for their anti-virulence activities. Lamivudine (LAM) is a synthetic nucleoside analogue used as an antiretroviral in treatment of HIV and can be used in treatment of HBV. The present study aimed to assess the anti-virulence activities of LAM against a clinically important pathogen Pseudomonas aeruginosa. The LAM’s antibiofilm and anti-virulence activities were evaluated. The impact of LAM on the quorum sensing (QS) systems which control the production of these virulence factors was assessed virtually and by quantification of the expression of QS-encoding genes. Furthermore, in vivo mice protection assay was conducted to attest the LAM's anti-pathogenic activity. The current findings elaborated the promising anti-pathogenic and anti-QS activities of LAM. LAM interfered with biofilm formation in P. aeruginosa PAO1 strain. Moreover, swarming motility and production of pyocyanin and protease were significantly diminished. At the molecular level, LAM downregulated the QS-encoding genes LasI, LasR, RhlR, PqsA and PqsR. Additionally, the detailed in silico docking and molecular simulation studies showed the considered high LAM's ability to bind and hinder the QS receptors in the P. aeruginosa. In an agreement with in vitro and in silico, the in vivo results showed the LAM full protection of mice against P. aeruginosa. In conclusion, LAM could be repurposed to be employed as adjunct therapy with traditional antibiotics for treating serious pseudomonal infections.